Beyond the River : A Practitioner Perspective - Grey, David; Sadoff, Claudia; Connors, Genevieve (World Bank, Washington, DC, 2016)
Building real cooperation on transboundary waters is always a lengthy and complex journey. Embracing cooperation is no simple task for a nation state, not least because of the perceived costs of the erosion of sovereignty, however small that erosion might be. While there are many examples of where cooperation is non-existent or weak, there are also examples of robust cooperation. This essay examines these questions through a practitioner’s lens to draw a few lessons from experience on why countries cooperate and how cooperation can be achieved.